Blinatumomab demonstrates MRD eradication in MRD-positive/chemotherapy-delayed pediatric B-ALL and high response in relapsed/refractory cases: a multicenter cohort study - Zhang, Na; Hu, Wenting; Dai, Yunpeng; Wang, Jian; Qu, Lijun; Wang, Dan; Liu, Bingju; Shao, Jingbo; Shen, Shuhong; Jiang, Hui (Frontiers in Immunology, 2025)
BackgroundBlinatumomab, a bispecific T-cell engager targeting CD3+ and CD19+, promotes T cell–mediated cytotoxicity against B-cell precursor acute lymphoblastic leukemia (B-ALL). While its efficacy is established in relapsed/refractory (R/R) disease, its role as preemptive therapy for minimal residual disease (MRD)–positive patients or those experiencing chemotherapy delays remains undefined. Predictors of treatment failure also require further investigation.MethodsIn this multicenter retrospective study, 105 patients who received blinatumomab were enrolled. Of these, 30 had R/R ALL, 21 were in complete remission (CR) with MRD positivity (CR-MRDpos), and 54 experienced chemotherapy delays. Eight patients received blinatumomab directly as reinduction therapy and 22 patients received burden-reduction chemotherapy prior to blinatumomab. In total, 11 children were in R/R status and 40 were in CR-MRDpos before treatment. Patients were subsequently bridged to stem cell transplantation, chimeric antigen receptor T-cell therapy (CAR-T), or protocol continuation. Treatment response was analyzed across CR-MRDpos, R/R, and CR with MRD negativity (CR-MRDneg). Immune reconstitution profiles (T-cell subsets, cytokine dynamics), cytogenetic markers, and clinical outcomes were assessed to identify predictors of treatment resistance.ResultsThe CR rate was 81.8% in R/R and 82.5% in CR-MRDpos patients (P = 1.000). Of 74 courses with CR-MRDneg, 73 remained MRD-negative during treatment. Univariate analysis revealed poor cytogenetics (P = 0.0001), CD19+ B-cell loss (P = 0.046), and BCR-ABL1 positivity (P = 0.002) as predictors of poor response. Cox regression analysis identified high MRD (P = 0.014), BCR/ABL1 (P = 0.065), and poor cytogenetics (P = 0.025) as independent risk factors. Blinatumomab significantly increased CD3+ T cells [0.96 (0.03–3.79) to 1.13 (0.26–7.74) ×109/L, P = 0.016], along with CD4+ [0.35 (0.01–1.39) to 0.47 (0.07–2.94) ×109/L] and CD8+ T cells [0.41 (0.01–2.39) to 0.56 (0.07–6.07) ×109/L] (P = 0.005 and P = 0.006, respectively).The 1-year event-free survival for CR-MRDneg, CR-MRDpos, and R/R patients was 97.8% ± 2.2%, 86.7% ± 6.2%, and 73.3% ± 8.1%, respectively (P = 0.001), while overall survival was 97.8% ± 2.2%, 100%, and 93.3% ± 4.6% (P = 0.029).ConclusionsBlinatumomab effectively clears MRD as preemptive therapy and serves as a bridging strategy during chemotherapy delays in pediatric B-ALL, while maintaining high response rates in R/R cases.